Comparison of thermoelectric properties of armchair germanene nanoribbon and armchair germanene nanomesh - Reza Kalami; Seyed Ahmad Ketabi (Progress in Physics of Applied Materials, 2023)
This study investigates the thermoelectric properties of pristine armchair germanene nanoribbons (AGeNR) and those defected by quantum antidot arrays (AGeNM). The researchers employed a tight-binding model and the non-equilibrium Green’s function formalism to conduct the study. AGeNM structures were created by introducing quantum antidot arrays in the form of symmetric and asymmetric rhomboid shapes in the central region of the pristine nanoribbons and their electrodes. The study reveals that different AGeNMs exhibit varying band gaps, influencing their electronic and thermoelectric behaviors. It is important to note that the presence of quantum antidot arrays introduces scattering of electrons and phonons in the nanoribbons, resulting in new thermoelectric properties such as the Seebeck coefficient, electrical conductance, electron and phonon thermal conductance, and ZT factor. The symmetry of the quantum antidot array shapes significantly influences the system’s thermoelectric properties. The study paves the way for the development of more efficient nanoscale thermoelectric devices.